Stale in the Saddle: CEO Tenure and the Match Between Organization and Environment - Miller, Danny (Management Science, 1991)
It has often been argued that an organization's strategy and structure must be tailored or matched to the challenges posed by its environment. Our research shows that this match is less likely to be achieved by long-tenured CEO's than by their counterparts with less tenure. It also suggests that the failure to match strategy and environment hurts financial performance. More specifically, CEO tenure related inversely to the prescribed match between organization and environment, especially in uncertain settings and where ownership was concentrated. The match between environment and strategy was in turn positively related to financial performance.